A paisagem cultural da Linha Leopoldina no Vale dos Vinhedos, Bento Gonçalves - RS - Lorandi, Roberta D'Agnoluzzo (My University, 2022)
The present research, developed for the Curricular Internship discipline of the Architecture and Urbanism course, aims to present the survey of the historical context and methodology necessary for the visual characterization of the landscape of the Linha Leopoldina, in the district of Vale dos Vinhedos, in Bento Gonçalves. The study is supported by the Museu do Imigrante in order to add information to the Laços Patrimoniais project. In addition, it proposes recognition for the appreciation of the local cultural landscape from the identification of its characteristics and peculiarities that make this place unique. Through several visits to the site and photographic records, it was possible to define connections and characterize the routes chosen in order to understand the visual structure of the site and thus establish the places with the greatest scenic value. In this way, it is possible to identify cultures, histories, memories and strengthen the local identity so that its preservation potential can be determined. This work also explores the visual qualities that especially value the area and that correspond to a specific social and spatial organization. [resumo fornecido pelo autor]
A presente pesquisa, desenvolvida para a disciplina de Estágio Curricular do curso de Arquitetura e Urbanismo, tem como finalidade apresentar o levantamento do contexto histórico e metodologia necessária para a caracterização visual da paisagem da Linha Leopoldina, no distrito do Vale dos Vinhedos, em Bento Gonçalves. O estudo é apoiado pelo Museu do Imigrante com o intuito de agregar informações ao projeto Laços Patrimoniais. Além disso, propõe o reconhecimento para a valorização da paisagem cultural local a partir da identificação de suas características e peculiaridades que tornam este local único. Por meio de diversas visitas ao local e registro fotográfico, foi possível definir conexões e caracterizar os percursos escolhidos a fim de compreender a estrutura visual do sítio e assim estabelecer os locais com maior valor cênico. Desta maneira, é possível identificar culturas, histórias, memórias e fortalecer a identidade local para que possa ser determinado o seu potencial de preservação. Este trabalho explora também as qualidades visuais que valorizam especialmente a área e que correspondem a uma organização social e espacial específica. [resumo fornecido pelo autor]
Keywords: Arquitetura; Patrimônio cultural - Bento Gonçalves (RS)